Conducting Matrices of the Poly(-O-Toluidine, PTOL) Film for Immobilizing Uricase - Dhony Hermanto; Nurul Ismillayli; Ulul Khairi Zuryati; Siti Raudhatul Kamali (Molekul, 2022)
Polyaniline, PANI as conducting polymer has been used as enzyme immobilization matrix in biosensors due to its excellent stability and electrochromic effects, conductivity, and redox reversibility. However, at pH above 4, the electron transfer ability and redox activity decrease, henceit is necessary to modify the PANI structure to increase the PANI pH range. In this study, the PANI derivative, the poly(-o-toluidine, PTOL) film was produced for the uricase immobilization matrix. This study aimed to develop a supporting material that maintains catalytic activity uricase with a facile and inexpensive procedure. The PTOL was prepared by using the chemical oxidative polymerization technique with ammonium persulfate (dissolved in 1.0 M HCl) as an oxidizing agent. The FTIR spectra confirmed the success of PTOL formation by the appearance of its characteristic peaks. The UV-Vis spectra indicated that PTOL was in an emeraldine state with a semi-crystalline structure that was shown by its XRD pattern. While, SEM analysis described that the PTOL film was uniform with some granular aggregation in its surface morphology, but there is no holes or porosity were found. The use of PTOL film as a uricase matrix could maintain the uricase activity against the substrate (uric acid, UA) with excellent analytical characteristics. Therefore, PTOL film could be used as conducting matrices for immobilizing enzymes (e.g. biosensors).